Trust-based evaluation in a market-oriented school system - Jonas Vlachos (Research Institute of Industrial Economics (IFN), 2018)
In Sweden, a trust-based system of school performance evaluation meets a market-oriented school system with liberal entry conditions for voucher-funded private providers. National standardized tests are graded at the local school and what ultimately matters to students are teacher-set grades. This paper finds that privately run free schools systematically set higher grades than public schools when controlling for their achievement on national tests. The differences between municipal and free schools are larger when more reliable tests are used to account for achievement. Differences in grading standards between providers are substantial and most of the performance advantage in teacher-set grades that free schools enjoy can be attributed to more generous grading. The results also indicate that different private providers do not necessarily respond symmetrically when faced with similar market conditions and act under the same regulatory regime.
Keywords: H44; I28; L51; 330; Private provision of public services; School performance evaluation; School vouchers